A General View on How the Orff Approach is Understood and Practiced in North Cyprus - Sülün, Erkan; Arıkhan, Emine (Journal of History Culture and Art Research, 2019)
In this study, perspectives on The Orff approach of those who attended the “I am Singing with Onur Erol” workshop were outlined to draw some inferences about their knowledge on The Orff approach. The level and the frequency of the usage of The Orff approach in their own classes were also examined.  Interviews were held with 19 attendees from the workshop. The method of content analysis was used to analyse the gathered data. It was observed that, although the attendees were frequent users of the Orff approach, their theoretical knowledge was limited. It was also determined that the attendees have more knowledge on the practice of the approach and therefore have more knowledge about general activities. This study also explored some of the problems associated with physical inadequacies of the classes where the Orff approach is taught, and the lack of essential instruments which are vital for the Orff approach.